La révolution palestinienne à l’épreuve de l’intime : Un captif amoureux de Jean Genet - Myriam Bendhif-Syllas (Itinéraires)
Two long stays in the Palestinian camps will allow the writer Jean Genet to be one of the rare Westerners to be able to testify of the life of the insurgents. This testimony, at the same time essay and autobiography, is entitled A Loving Captive. Far from the expected panegyric, from the committed paper waited by the defenders of the Palestinian cause, Genet distances himself: he will not be a soldier of the revolution, he will not be one of the thinkers. Indeed, he will define himself rather as an observer and a storyteller while giving his own political vision of the conflict. It is at the heart of the intimate that Genet intends to find his vision of Palestine: he articulates the memory with the fiction in a “report-mirror.” Defender of a revolution while keeping a critical and outside position, outside the history while living it, Jean Genet reports an intimate experience, that of a man and an artist in a people with whom he desperately fell in love.